2021
DOI: 10.3390/ijms22031332
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of the Cancer-Associated lncRNA Snhg15 Is Modulated by EphrinA5-Induced Signaling

Abstract: The Eph receptor tyrosine kinases and their respective ephrin-ligands are an important family of membrane receptors, being involved in developmental processes such as proliferation, migration, and in the formation of brain cancer such as glioma. Intracellular signaling pathways, which are activated by Eph receptor signaling, are well characterized. In contrast, it is unknown so far whether ephrins modulate the expression of lncRNAs, which would enable the transduction of environmental stimuli into our genome t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(58 citation statements)
references
References 72 publications
3
54
0
Order By: Relevance
“…The bidirectional signaling mediated by ephrinA5 and EphA4 also offers other possible therapeutic opportunities. For example, ephrinA5 mimetics, like 150D4 , could find applications also in oncology, including glioma and colon cancers, where ephrinA5 was found to act as a tumor suppressor, interfering with EGFR. Unlike ephrinA5, 150D4 is more selective for the EphA4 subtype, and being a synthetic agent, it is readily available for translation into a therapeutic agent.…”
Section: Discussionmentioning
confidence: 99%
“…The bidirectional signaling mediated by ephrinA5 and EphA4 also offers other possible therapeutic opportunities. For example, ephrinA5 mimetics, like 150D4 , could find applications also in oncology, including glioma and colon cancers, where ephrinA5 was found to act as a tumor suppressor, interfering with EGFR. Unlike ephrinA5, 150D4 is more selective for the EphA4 subtype, and being a synthetic agent, it is readily available for translation into a therapeutic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebellar granule (CB) cells (Fossale et al, 2004) were cultured as previously described (Pensold et al, 2021). Briefly, CB cells were incubated in Dulbecco’s modified Eagle medium (DMEM) with high glucose (#11965084, Gibco), supplemented with 10% fetal bovine serum (FBS) (#S1810, Biowest), 1× GlutaMAX™lJ (#35050038, Thermo Scientific) and 24 mM KCl at 33LJ, 5% CO 2 and 95% relative humidity.…”
Section: Methodsmentioning
confidence: 99%
“…For Adamts14, the sequence-based predictions (method described in Pensold et al, 2021; sequences presented in Supplementary Table S2) suggested two slightly different alternatives for the 15-nucleotide binding mode, which were used to generate the two models, Adamts14 -1 and Adamts14 -2. For Ncam1, a 15-nucleotide sequence ( Ncam1 ) as well as an extended sequence ( Ncam1 -ext) with additional base pairs (see Supplementary Table S2) were chosen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately in clear cell renal cell carcinoma (ccRCC), DNA hypomethylation might play a notable role in elevating SNHG15 transcription by substantially modulating its expression level. In the human medulloblastoma cell line DAOY, SNHG15 was modulated by EphrinA5-induced signal transduction, with EphrinA5 stimulation significantly reduced SNHG15 expression which might be relevant for the regulation of tumorigenic processes in the context of glioma ( 126 ).…”
Section: Regulatory Network Of Snhg15mentioning
confidence: 99%